Enhanced 5D0 → 7F4 transition and optical thermometry of garnet type Ca3Ga2Ge3O12:Eu3+ phosphors. Issue 6 (16th April 2018) - Chi, Fengfeng; Wei, Xiantao; Zhou, Shaoshuai; Chen, Yonghu; Duan, Changkui; Yin, Min
Abstract : Emission spectra of Ca3 Ga2 Ge3 O12 :Eu 3+ phosphors at room temperature (a) and the temperature range of 160–360 K (b). Abstract : The garnet type phosphors of Eu 3+ doped Ca3 Ga2 Ge3 O12 were synthesized via conventional solid state reaction techniques. The phase purity and luminescence properties of the fabricated phosphors were characterized by X-ray powder diffraction, photoluminescence excitation and emission spectra, temperature dependent emission spectra as well as luminescence decay curves. The phosphors show enhanced red emission from a 5 D0 → 7 F4 transition of Eu 3+ under the excitation of 394 nm. The unusual 5 D0 → 7 F4 intensity was explained by structural analysis. The emission intensity of the phosphors increases with the concentration of Eu 3+ until the quenching concentration of 10 mol%. Excited by a pulsed laser of wavelength 610.8 nm, the emission intensity of the 5 D0 → 7 F4 transition increases monotonously as the temperature increases in the range of 160–360 K. The temperature dependent fluorescence behavior was investigated. The relative sensitivity reaches the maximum value of 3.66% K −1 at 160 K and reaches 1.04% K −1 at 300 K. The results show that the garnet type Ca3 Ga2 Ge3 O12 :Eu 3+ phosphor is a promising material for the application of optical thermometry.